RUH AL-MUDARRIS: FONDASI KARAKTER SISWA YANG UNGGUL DAN BERTANGGUNG JAWAB.: RUH AL-MUDARRIS: FONDASI KARAKTER SISWA YANG UNGGUL DAN BERTANGGUNG JAWAB. - Umi Rosyidah (Jurnal Staika: Jurnal Penelitian dan Pendidikan, 2024)
Education serves as the primary foundation in shaping students' characters. Teachers play a crucial role in the realm of education. Thus, issues related to educators or teachers should be prioritized. This research aims to discuss the concept of Ruhul Mudarris in shaping students' characters. The qualitative method is employed with a literature review approach, drawing data from various primary and secondary sources. The study illustrates that the "ruh" or soul of a teacher holds greater significance than the teacher themselves in the learning process. This aligns with the philosophy, "At-Thoriqotu ahammu min al-maddah, al mudarris ahammu min at-thoriqoh, wa ruhul mudarris ahammu minal mudarris binafsihi."